Stories and minds : cognitive approaches to literary narrative - Bernaerts, Lars, 1980-; Geest, Dirk de, 1957-; Herman, Luc; Vervaeck, Bart (Frontiers of narrative., 2013)
How do narratives draw on our memory capacity? How is our attention guided when we are reading a literary narrative? What kind of empathy is triggered by intercultural novels? A cast of international scholars explores these and other questions from an interdisciplinary perspective in this work, a collection of essays that discusses research in the field of cognitive narrative studies. Recent findings in the philosophy of mind and cognitive psychology, among other disciplines, are integrated in fresh theoretical perspectives and illustrated with accompanying analyses of literary fiction. Pursuing such topics as narrative gaps, mental simulation in reading, theory of mind, and folk psychology, these essays address fundamental questions about the role of cognitive processes in literary narratives and in narrative comprehension. This book reveals the rich possibilities for research along the nexus of narrative and mind. --